THE INFLUENCE OF XENOBIOTICS ON THE COURSE OF ST-ELEVATION MYOCARDIAL INFARCTION AND THE STRUCTURE OF INTRACORONARY THROMBI - Sokolov, M.Y.; Besh, D.I. (World of Medicine and Biology, 2023)
Xenobiotics are significant risk factor for the development of acute myocardial infarction. To elucidate the influence of xenobiotics on the course of ST segment elevation myocardial infarction and the peculiarities of intracoronary thrombi structure. 100 patients (mean age 57.81±10.26 years) with ST segment elevation myocardial infarction were included. All participants underwent manual thromboaspiration during percutaneous coronary intervention. Thrombi were evaluated morphologically. Patients with exposure to xenobiotics were significantly younger (55.29±10.86 vs. 61.25±11.14 years; P